RELATIONSHIP WITH MOTHER WORKING WITH EARLY REMAINING INDOROWATI VILLAGE DISTRICT EAST DISTRICT NORTH LAMPUNG DISTRICT IN 2017 - Santi Mutiara; Yona Desni Sagita (Journal Aisyah University, 2018)
WHO recorded the world's IMR rate of 35 per 1000 live births. This figure is still far below the target of the fifth Millennium Development Goal (MDGs), which is 23 per 1000 live births in 2015.